GOAL PROGRAMMING SEBAGAI DECISION SUPPORT SYSTEM TINGKAT KESEHATAN BANK PT BANK BUKOPIN, TBK - Dewi, Aprilia Sintya; Paramu, Hadi; Endhiarto, Tatok (BISMA: Jurnal Bisnis dan Manajemen, 2017)
Abstract: This research aimed to analyze the changes in several objective priorities as the banking targets in the decision making process. The research applied goal programming model and based on the experiments on the financial data or ratios. The objective functions of the research were the ratios used to asses bank health level, namely: capital, Capital Adequacy Ratio (CAR), asset quality, Return on Assets (ROA), Return on Equity (ROE), Net Interest Margin (NIM), Operational Cost compared to Operating Income (BOPO) and Loan to Deposit Ratio (LDR). Results show that only capital and LDR targets achieved predominantly on a variety of priority setting. While the targets of CAR, asset quality, ROE, and NIM are not achieved predominantly on a variety of priority setting. Keywords: Capital, CAR, Asset Quality, ROA,ROE, NIM, BOPO, LDR, Financial Health Level.